(untitled) (Revista científica Olimpia, 2020)
The objective of the present study was to analyze the directionality and effectiveness of the serve, in the Villa Clara school women’s volleyball team during the 2018 western zonal national championship. The characteristics of the serves performed in the competition by the players of this team, to nine areas delimited by previous studies. To do this, an Ad-hoc instrument was developed that facilitated the collection of information and the subsequent analysis of the results. The contributions of this research are given by the characterization of the areas of the field with the highest incidence in the performance of the service on the rivals, which will determine the values ​​related to the execution of the service, to direct the training actions of this team. The information obtained constitutes reference values ​​for the team and the category in Cuba.